Analysis Of The Property Of Bilingual Language Education In Bilingualist Communities - Siagian, Yosua Marasi Parningotan; Sudiana, I Nyoman; Putrayasa, Ida Bagus (Jurnal Mamangan, 2023)
This study aims: to describe the forms of language politeness in the bilingualism community and describe the factors that cause impoliteness in the bilingualism community in Suka Village, Tigapanah District, Karo Regency. This type of research is research that uses qualitative methods because the research data is descriptive in nature so it does not involve numbers in it. In other words, the research method used by the researcher tries to study or describe in depth the phenomenon being studied. In this case the researcher can approach the informant intensely so that the researcher obtains factual data. The results of this study are as follows: 1) Found forms of language politeness in the bilingualism community in Suka village, Tigapanah District, Karo Regency, namely: 6 data maxims of wisdom, 12 data maxims of generosity, 6 data maxims of modesty, 6 data maxims of appreciation 6 data, consensus maxim 14 data, and sympathy maxim 6 data. 2) Factors that affect the violation of the principle of language politeness in the bilingualism community in Suka village, Tigapanah District, Karo Regency, namely: direct criticism using harsh words, emotional encouragement of the speaker, protective of opinions, deliberately accusing the interlocutor, and deliberately cornering partners said.